A Review of Component and Pharmacology Activities of Black Garlic - Novitaria Br Sembiring; Yoppi Iskandar (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Black garlic is garlic fermented in high temperature and humidity, and the fermentation compound chemical in garlic changes to new chemicals, such as S-allyl cysteine (SAC), S-allylmercapto-cysteine, and arginine. The color changed to dark brown during the aging period because of the Maillard reaction, known as non-enzymatic browning reaction. Black garlic has 57.14% of fructose, 6.78% of glucose, and 7.62% of sucrose, which were mainly saccharides in black garlic to answer for its sweet taste. It is such a pharmacological activity which contains antioxidant, anti-cancer, hepatoprotective, can improve the immune system, reduce hyperglycemia, dyslipidemia, and anti-allergic. We summarize the current knowledge of a change in the components, bioactivity, production, and applications of black garlic, as well as the proposed future prospects on their possible applications as a functional pharmacy product.